EFEKTIVITAS PENGGUNAAN INSTAGRAM SEBAGAI MEDIA KOMUNIKASI PUBLIK DI PT PERTAMINA (PERSERO) - Sabriena; Supama Wijaya, Abung (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
The rapid advancement of the digital era compels companies to leverage social media as an effective public communication channel. This study evaluates the effectiveness of PT Pertamina’s Instagram in disseminating information, fostering engagement, and strengthening corporate image. A descriptive qualitative approach was employed, including observation of the official Instagram account, interviews with the social media management team, and relevant literature review. Data were thematically analyzed to identify content planning, production, and interaction patterns. Results demonstrate that Instagram offers extensive reach and two-way interaction through visual features such as Reels and IG Story, and fosters emotional resonance through authentic storytelling and stakeholder voices. A structured workflow—comprising planning, listing and collecting data, content creation, approval, and posting—ensures message consistency. However, corporate-centric content, high interaction volumes, and algorithm changes pose significant challenges. SWOT analysis revealed strengths in mass reach and responsive transparency, weaknesses in human interest elements, opportunities for external collaboration, and threats from hoaxes and content competition. Recommendations include diversifying content, strengthening moderation SOPs, and optimizing interactive features to enhance public participation and maintain relevance.